TechTip: Mo-Ap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The Micro-Banking Open Architecture Project (Mo-Ap) is a new initiative to define and develop open source standards, software and documentation for microfinance institutions (MFIs) worldwide.